Evaluating the best value pilot programme: measuring `Success' and `Improvement' - David, Howard; Martin, Steve (2002)
In 2000 new `Best Value' duties were placed on local government, seeking continuous improvement in local public services. This article draws upon our experience of evaluating the Best Value pilot programme, which took place ahead of implementation of the legislation. The results of the pilot programme influenced the Best Value guidance, demonstrated that the Best Value framework can deliver improvements and help to shape ministerial expectations about the likely speed of change. However, the challenges associated with measuring the extent and level of service improvement with precision have a number of important implications for the future development of the regime. - Reproduced.
Keywords: Local government